Pagans in late Roman Halikarnassos II - Isager, Signe (Proceedings of the Danish Institute at Athens, 1995)
This article will provide a preliminary presentation and discussion of the mosaic inscriptions found in the pavements of a suggests that the inscriptions testify to an orphic/neo platonic milieu in 5th century Halikarnassos and to a spiritual if not personal presence of the Egyptian poet Nonnos in the town. The inscriptions to be presented were found during the Danish excavations in Bodrum in 1991 and 1992; they were cleaned and restored in the campaign of 1993.